Long-Circulating Nanoemulsion with Oxygen and Drug Co-Delivery for Potent Photodynamic/Antibiotic Therapy Against Multidrug-Resistant Gram-Negative Bacterial Infection - Li X; Hou X; Zhang S; Xiong J; Li Y; Miao W (International Journal of Nanomedicine)
Xiaolong Li,1 Xinyi Hou,2 Siqin Zhang,1 Jianming Xiong,1 Yuanyuan Li,2,3 Wenjun Miao1,4 1School of Pharmaceutical Sciences, Nanjing Tech University, Nanjing, 211816, People’s Republic of China; 2School of Pharmacy, Hainan Medical University, Haikou, Hainan, 571199, People’s Republic of China; 3NHC Key Laboratory of Tropical Disease Control, Hainan Medical University, Haikou, Hainan, 571199, People’s Republic of China; 4State Key Laboratory of Materials-Oriented Chemical Engineering, Nanjing Tech University, Nanjing, 211816, People’s Republic of ChinaCorrespondence: Yuanyuan Li, School of Pharmacy, Hainan Medical University, Haikou, Hainan, 571199, People’s Republic of China, Tel/Fax +86-0898-66968120, Email liyuanyuan@hainmc.edu.cn Wenjun Miao, School of Pharmaceutical Sciences, Nanjing Tech University, Nanjing, 211816, People’s Republic of China, Tel/ Fax +86-25-58139942, Email miaowj@njtech.edu.cnPurpose: Compared to conventional photodynamic therapy (PDT), oxygen-affording PDT represents a promising strategy for treating multidrug-resistant (MDR) gram-negative bacterial infections due to its enhanced sensitization ability towards bacteria and amplified therapeutic efficacy. Over the last decade, various nanoplatforms for the co-delivery of oxygen and photosensitizers have been developed. However, their application in the treatment of infectious diseases is hampered by their poor stability and easy clearance by the reticuloendothelial system (RES).Methods: To address these obstacles, we reported an erythrocyte membrane (EM) camouflaged nanoemulsion containing chlorin e6 (Ce6) and perfluorocarbon (FDC), named ECF, showing good colloidal stability and long-circulating potential, making it suitable for fighting against MDR Gram-negative bacterial infections. The nanoemulsion was fabricated and characterized. The oxygen loading and release performance, photodynamic activity, and bactericidal performance of ECF against Acinetobacter baumannii (A. baumannii) were evaluated. Furthermore, the antiphagocytosis profile was tested in vitro using Raw 264.7 cells. In addition, the pharmacokinetic behavior and therapeutic efficiency of ECF were studied in vivo.Results: ECF exhibited superior oxygen loading and release behavior, potent photodynamic activity, and negligible toxicity to mammalian cells. Upon light irradiation, the antibacterial rate of preoxygenated-ECF reached 98% at 40 μg mL− 1 of Ce6 and the bactericidal activity of preoxygenated-ECF and Gen was 3.3 folds higher than that of Gen. Furthermore, ECF could effectively inhibit uptake by phagocytes and circulate in the blood 1.5-fold longer than that of nanoemulsion without EM modification (CF) following intravenous administration. In addition, preoxygenated-ECF combined with antibiotic plus light irradiation showed prominent therapeutic efficacy in treating A. baumannii-induced acute peritonitis, accompanied by good biocompatibility in vivo.Conclusion: Our results provide a novel paradigm for evading immune clearance, prolonging retention time and improving synergetic bactericidal capacity in combination with PDT and antibiotic therapy against planktonic bacteria and gram-negative bacterial infections.Keywords: Gram-negative bacterial infection, multidrug-resistant, photodynamic therapy, oxygen affording, long circulation